Ethnic and socioeconomic determinants of dementia risk: A nested case‐control study in the population of East London: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Bothongo, Phazha LK; Jitlal, Mark; Parry, Eve; Foote, Isabelle F; Waters, Sheena; Dobson, Ruth; Noyce, Alastair J; Bestwick, Jonathan P; Marshall, Charles R; ,
Abstract: Background: The influence of ethnicity and socioeconomic status on dementia risk, and the extent to which this is mediated by known risk factors remain incompletely understood. We addressed this issue using health records data from the diverse and deprived population of East London (<50% White and >50% in the most deprived quintile of the UK). Method: We performed a nested case‐control study in over 1, 000, 000 East London inhabitants. We identified 4137 cases of all cause dementia, and matched on age and gender to controls with ratio 1:4. Logistic regression was used to calculated odds ratios (ORs) for exposures of ethnicity and UK Index of Multiple Deprivation (IMD), before and after inclusion in the model of established modifiable risk factors (type II diabetes, hypertension, smoking, body mass index, depression and hearing loss). In order to reflect the relative importance of known modifiable risk factors in this deprived multiracial population, we calculated weighted population attributable fractions (PAF) for each factor. Result: Risk of dementia was higher in the Black and South Asian groups relative to White (ORs (95%CI) Black 1.43 (1.31, 1.56), South Asian 1.17 (1.06, 1.29)). Risk of dementia was reduced in all IMD quintiles relative to the most deprived (ORs (95%CI) 2nd 0.71 (0.66, 0.77), 3rd 0.52 (0.44, 0.60), 4th 0.71 (0.53, 0.94), 5th 0.59 (0.38, 0.87)). The effects of ethnicity and deprivation persisted after adjusting for known risk factors. Weighted PAFs for modifiable risk factors were notably higher in this population for depression (9.2%) and diabetes (6.2%) than those estimated in the Lancet Commission meta‐analyses (4% and 1.2% respectively). Conclusion: Membership of non‐White ethnic groups and socioeconomic deprivation are important determinants of dementia risk, with effects larger than many of the more established risk factors. These effects cannot be completely accounted for by known modifiable risk factors and further work is required to establish the responsible mechanisms. Depression and diabetes are of greater relative importance, and should be prioritised as targets for dementia prevention in more diverse and deprived populations.